Karakteristik Bakso Ikan Bilis (Stolephorus hamiltonii) dengan Komposisi Bahan Pengikat yang Berbeda - Atikasari, Dwi; Rahayuini, Tri; Maherawati, Maherawati (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPA, 2022)
Making anchovies meatballs is an effort to diversify and utilize fish as a source of protein to be processed into food that the community likes. Making meatballs requires a binder which is generally tapioca flour. The utilization of flour from local ingredients needs to be done to determine its effect on the anchovy meatballs' characteristics. The purpose of this study was to determine the physicochemical characteristics (moisture content, ash content, protein content, water holding capacity), microbiological (microbial count), and sensory (color, taste, aroma, texture, and overall preference) of anchovy meatballs with various ratios binder of sago starch and yellow sweet potato flour. The research design used a one-factor Randomized Block Design (RBD) comparing sago starch and sweet potato flour with seven treatment levels (0:0, 30:30, 25:35, 20:40, 15:45, 10:50, 5:55) and three replication. The data obtained were analyzed statistically using ANOVA (?=5%), and if there were an effect, it would be continued with the BNJ test (?=5%). The results showed that the binder ratio did not affect the water content, ash content, protein content, and water holding capacity of anchovies meatballs. The total number of microbes in anchovies meatballs is still within the safe limits for consumption, according to SNI 7266:2014. Sensory attributes affected by the ratio of binders are taste, aroma, texture, and overall appearance, while color attributes are not affected by the ratio of binders. The best treatment was the ratio of sago starch and sweet potato flour 25:35 with the characteristics of water content 57.71%, ash content 4.79%, protein content 4.35%, water holding capacity 48%, TPC 9.90x104 CFU/g, color 3.17 (slightly like), taste 2.97 (dislike), aroma 3.23 (slightly like), texture 3.20 (slightly like), and overall preference 3.27 (slightly like).